Dual silencing of EGFR and HER2 enhances the sensitivity of gastric cancer cells to gefitinib. Issue 8 (24th April 2018) - Wang, Liying; Zhang, Hongfeng; Zheng, Jiaxin; Wei, Xiaoli; Du, Jingwen; Lu, Haibo; Sun, Qiuying; Zhou, Weiyu; Zhang, Rui; Han, Yu
Abstract : Gefitinib exhibits very limited efficacy in gastric cancer (GC). Indeed, the limited clinical results obtained with gefitinib alone justify investigation of additional therapeutic strategies. Here, we demonstrate the importance of EGFR and HER2 in GC malignancy using RNA interference (RNAi). Additionally, we explored the ability of RNAi targeting EGFR and HER2 to enhance the sensitivity of GC cells to gefitinib. Specific small interfering RNAs (siRNAs) significantly inhibited mRNA and protein expression of target genes. EGFR‐specific siRNA, EGFR/HER2 siRNAs, and gefitinib inhibited growth and induced apoptosis in GC cell lines in a dose‐dependent manner. In contrast, resistance to HER2‐siRNA‐induced growth inhibition and apoptosis was linked to compensatory activation of EGFR. Moreover, gefitinib dramatically reduced p‐EGFR and p‐HER2 levels in the cell lines tested, and sensitivity to gefitinib was enhanced through dual silencing of EGFR and HER2 via suppression of AKT and ERK activation. These findings are in agreement with the profound inhibitory effect of gefitinib on activation of both EGFR and HER2. Overall, EGFR/HER2 knockdown by siRNAs further decreased the growth of GC cells treated with gefitinib alone, confirming that single‐agent drug targeting does not achieve a maximal biological effect. The combination of gefitinib with EGFR/HER2 siRNAs should be further investigated as a new strategy for the treatment of GC and other EGFR/HER2‐dependent cancers.